Cytotoxic Activity and Memory T Cell Subset Distribution of in vitro-Stimulated CD8+ T Cells Specific for HER2/neu Epitopes - Kuznetsova, Maria; Lopatnikova, Julia; Shevchenko, Julia; Silkov, Alexander; Maksyutov, Amir; Sennikov, Sergey (Frontiers in Immunology, 2019)
Minimal residual disease remaining after resection of primary tumors can lead to tumor recurrence and metastasis, increasing mortality and morbidity rates among cancer patients. Thus, there is a need for new technologies for recognition and elimination of single cancer cells remaining in a patient’s body after radiation therapy, chemotherapy, or surgical resection. Effector CD8+ T cells, also commonly known as cytotoxic T lymphocytes (CTLs), play a key role in antitumor cellular immunity and, when properly activated, are able to effectively destroy tumor cells. The aims of this study were to obtain CD8+ CTLs specific for the HER2/neu epitopes E75 and E88, and to assess the cytotoxic activity and composition of these cells in terms of the distribution of memory T-cell subsets. We obtained HER2-specific CD8+ T cells and assessed T cell subset distribution among them including naive T cells (TN), central memory T cells (TCM), effector memory T cells (TEM), stem cell-like memory T cells (TSCM) and terminally-differentiated T cells (TEMRA) via eight-color flow cytometry. HER2-specific CTLs were largely (~40–50%) represented by TSCM cells, a population capable of mounting pronounced antitumor immune responses due to a combination of effector function and self-maintenance. In comparison with activated peripheral blood mononuclear cells (PBMCs) and bulk CD8+ T cells, HER2-specific CTLs exhibited greater cytotoxicity against the HER2-expressing human breast adenocarcinoma cell line MCF-7 and produced higher levels of IFN-γ in response to tumor cells. We also showed the presence of HER2-specific CTLs in healthy individuals and increase in them in HER2-positive breast cancer patients. Collectively, our results suggest that HER2-specific CD8+ T cells isolated using this approach could be used for adoptive T-cell transfer to eliminate tumor cells and prevent metastasis and relapse in patients with HER2-overexpressing cancers.